2020
DOI: 10.1371/journal.pcbi.1008048
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure-induced atrial remodelling promotes electrical and conduction alternans

Abstract: Heart failure (HF) is associated with an increased propensity for atrial fibrillation (AF), causing higher mortality than AF or HF alone. It is hypothesized that HF-induced remodelling of atrial cellular and tissue properties promotes the genesis of atrial action potential (AP) alternans and conduction alternans that perpetuate AF. However, the mechanism underlying the increased susceptibility to atrial alternans in HF remains incompletely elucidated. In this study, we investigated the effects of how HF-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
(120 reference statements)
2
3
1
Order By: Relevance
“…Furthermore, we detected the key proteins that affect electrical remodeling, including SERCA2α, PLB, CAMK II, and Kv1.5. SERCA2α and PLB influence cardiomyocyte repolarization and depolarization by regulating diastolic calcium channels, while CAMK II and Kv1.5 activate K + currents and affect cell membrane excitability 33–36 . Our data confirmed that intramyocardial Tx inhibited sarcoplasmic reticulum calcium leakage by lowering PLB and CAMK II expression and increasing SERCA2α expression to prevent arrhythmia, and the stimulating effect of intramyocardial Tx based on Kv1.5 may be a potential physiological advantage for regulating myocardial excitability.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, we detected the key proteins that affect electrical remodeling, including SERCA2α, PLB, CAMK II, and Kv1.5. SERCA2α and PLB influence cardiomyocyte repolarization and depolarization by regulating diastolic calcium channels, while CAMK II and Kv1.5 activate K + currents and affect cell membrane excitability 33–36 . Our data confirmed that intramyocardial Tx inhibited sarcoplasmic reticulum calcium leakage by lowering PLB and CAMK II expression and increasing SERCA2α expression to prevent arrhythmia, and the stimulating effect of intramyocardial Tx based on Kv1.5 may be a potential physiological advantage for regulating myocardial excitability.…”
Section: Discussionsupporting
confidence: 75%
“…An uncharacteristic discordant alternans can be observed under the action of ATO ( Supplementary Figure S2 ). The tissue alternans in this study were not as obvious as those in heart failure-associated atrial alternans research ( Zhao et al, 2020 ) because except for single cell characters, the decreased CV in atrial tissue was also an essential factor in inducing tissue alternans. There is no evidence that ATO reduced the CV in ventricular tissue, so the alternans did not easily occur in this present simulation.…”
Section: Discussioncontrasting
confidence: 59%
“…Their results indicated that AF remodeling enhanced spontaneous single-cell Ca 2+ release, prolonged the refractory period of the Ca 2+ transient, increased the slope of the Ca 2+ transient restitution curve, and eventually predisposed hearts to Ca 2+ transient alternans [ 23 ]. Furthermore, in a recent simulation study, Zhao et al [ 24 ] revealed that HF-induced atrial electrical remodeling increased Ca 2+ transient amplitude and SR Ca 2+ concentration. They demonstrated that the enhanced SR Ca 2+ reuptake was the primary reason that HF-induced atrial electrical remodeling increased susceptibility to atrial alternans [ 24 ].…”
Section: Investigating Mechanisms Of Atrial Alternansmentioning
confidence: 99%
“…Furthermore, in a recent simulation study, Zhao et al [ 24 ] revealed that HF-induced atrial electrical remodeling increased Ca 2+ transient amplitude and SR Ca 2+ concentration. They demonstrated that the enhanced SR Ca 2+ reuptake was the primary reason that HF-induced atrial electrical remodeling increased susceptibility to atrial alternans [ 24 ].…”
Section: Investigating Mechanisms Of Atrial Alternansmentioning
confidence: 99%